Um estudo exploratório sobre a modelagem arquitetural de sistemas de informação considerando os aspectos funcionais da usabilidade - Costa, Alex Felipe Ferreira; Marques, Anna Beatriz dos Santos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Usability is a quality attribute of systems which are easy to be understood, easy to be used and attractive to users. Usability impacts more than just user interface, also influencing the system behavior and features, affecting the system architecture. There are few studies that investigate the incorporation of usability in system design and architecture. In this sense, this paper presents an exploratory study on the system architectural design aligned to functional usability features. The study was conducted in academic environment, while groups of students in a software architecture discipline conducted system architecture projects of web information systems. The groups adopted existing guidelines for architectural modeling considering usability. The results indicated a tendency to specify functional usability features related to warning, multi-level help and to feedback on the system status. However, such requirements were not adequately represented in the architectural solutions. The students recognized the importance of usability in system architecture, although they reported difficulties in usability incorporation. We observed the need for more guidelines for decision-making when integrating usability in system architecture.